Shops and the city - Stan Veuger; Daniel Shoag (American Enterprise Institute (AEI), 2016)
We report three findings: (1) Using evidence from chain bankruptcies and data on 12-18 million establishments per year, we show that large retailers produce significant positive spillovers. (2) Local governments respond to the size of these externalities. When a town's boundaries allow it to capture a larger share of retail spillovers, it is more likely to offer retail subsidies. (3) These subsidies crowd out private-sector mechanisms that also subsidize large retailers, such as shopping malls. These facts provide powerful evidence of the Coase theorem at work and highlight a concern for local development policies even when externalities can be targeted.
Keywords: A; 330; subsidies; retail